2015
DOI: 10.4103/2231-0746.175746
|View full text |Cite
|
Sign up to set email alerts
|

Lemierre's syndrome from odontogenic infection: Review of the literature and case description

Abstract: Lemierre's syndrome (LS) is a rare potentially fatal sequel of head and neck infection, classically described as thrombophlebitis of the internal jugular vein (IJV) with cervical space infection extending into the thorax. Our objective was to answer the clinical question: “Does Lemierre syndrome (LS) from odontogenic infection differ from nonodontogenic LS in regard to clinical sequence, treatment, and survival.” We reviewed the literature on the management of LS over the last two decades, with a focus on LS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…2 Mortality, however, has been significantly decreased from as high as 90% in the preantibiotic era. 3 Our patient represents a unique case of an already rare disease for several reasons. First, this patient presented at the age of 80.…”
Section: Discussionmentioning
confidence: 96%
“…2 Mortality, however, has been significantly decreased from as high as 90% in the preantibiotic era. 3 Our patient represents a unique case of an already rare disease for several reasons. First, this patient presented at the age of 80.…”
Section: Discussionmentioning
confidence: 96%
“…An epidemiological and therapeutic comparison of Lemierre's syndrome associated and not associated with an odontogenic infection revealed that F. necrophorum is not the only causal microorganism and that Lemierre's syndrome of primary odontogenic origins can have lower virulence potential . However, aggressive antibiotic therapy associated with surgical interventions and elimination of the focus of infection remains the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed Lemierre's syndrome, an illness characterized by internal jugular vein thrombophlebitis with anaerobic bacteremia, classically Fusobacterium necrophorum. 1,2 Our patient acutely developed clinical and radiographic evidence of bilateral cavernous sinus thrombosis, a rare complication of Lemierre's syndrome that may be life-threatening if not promptly recognized and treated. He also had focal pachymeningitis and septic lung foci, illustrating the diverse potential clinical manifestations of this disease.…”
mentioning
confidence: 93%
“…On thorough oral examination, the dentistry service found and extracted a residual root, suggesting an odontogenic source. 2 Marked clinico-radiographic improvement occurred after six weeks of meropenem 2 grams IV q8h, metronidazole 500 mg PO TID, and rivaroxaban 20 mg PO daily, emphasizing the importance of accurate diagnosis and treatment.…”
mentioning
confidence: 99%